Sparse 3D contrast-enhanced whole-heart imaging for coronary artery evaluation - Ansari, Uzair; Janssen, Sonja; Baumann, Stefan; Borggrefe, Martin; Waldeck, Stephan; Schönberg, Stefan; Papavassiliu, Theano; Overhoff, Daniel (Herz, 2023)
We investigated the feasibility of evaluating coronary arteries with a contrast-enhanced (CE) self-navigated sparse isotropic 3D whole heart T1-weighted magnetic resonance imaging (MRI) study sequence.